2021
DOI: 10.20450/mjcce.2021.2414
|View full text |Cite
|
Sign up to set email alerts
|

Trinuclear silver(I) complex of non-steroidal anti-inflammatory drug naproxen: Synthesis, characterization, and in vitro cytotoxicity

Abstract: Herein, a new silver(I) complex with the non-steroidal anti-inflammatory drug naproxen and nitrogen donor 3-picoline ligands was synthesized, characterized, and subsequently tested for its cytotoxicity against different types of cancer cell lines. Elemental analysis, Fourier transform infrared spectroscopy, thermal, and proton nuclear magnetic resonance techniques showed that the molecular formula of the prepared complex is bis(3-picoline)tris(-naproxenato)trisilver(I) and naproxen ligands bind to silver ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Hence, A549 cells were selected to further test the activity of complex 1 in the following experiments. Complex 1 has better antitumor activity, probably because its hydrophobicity is the strongest among the four compounds, which enables 1 to cross the cell membrane more easily. , The cytotoxicity of complex 1 to the A549 cell line is higher than that of the six reported Ag­(I)–NSAID complexes, but complexes 2 , 3 , and 4 exhibit less toxicity to A549 cells than those six compounds. Complex 1 displays stronger activity against the HepG-2 cancer cells compared with [AgH­(nif) 2 ], [Ag­(tpp) 2 (tolf)], and [Ag­(tpp) 2 (ibu)]; however, the four complexes ( 1 , 2 , 3 , and 4 ) show lower cytotoxicity in HepG-2 than other silver­(I) compounds of nonsteroid anti-inflammatory drugs. ,, Complexes 1 , 2 , 3 , and 4 have relatively low toxicity toward MCF-7 cells, and their IC 50 values are less than those of the previously reported silver­(I)–NSAID complexes. ,,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, A549 cells were selected to further test the activity of complex 1 in the following experiments. Complex 1 has better antitumor activity, probably because its hydrophobicity is the strongest among the four compounds, which enables 1 to cross the cell membrane more easily. , The cytotoxicity of complex 1 to the A549 cell line is higher than that of the six reported Ag­(I)–NSAID complexes, but complexes 2 , 3 , and 4 exhibit less toxicity to A549 cells than those six compounds. Complex 1 displays stronger activity against the HepG-2 cancer cells compared with [AgH­(nif) 2 ], [Ag­(tpp) 2 (tolf)], and [Ag­(tpp) 2 (ibu)]; however, the four complexes ( 1 , 2 , 3 , and 4 ) show lower cytotoxicity in HepG-2 than other silver­(I) compounds of nonsteroid anti-inflammatory drugs. ,, Complexes 1 , 2 , 3 , and 4 have relatively low toxicity toward MCF-7 cells, and their IC 50 values are less than those of the previously reported silver­(I)–NSAID complexes. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…27−29 Recently, metal complexes based on NSAIDs have gained great interest, and they are often more active than free NSAIDs. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]47,[80][81][82][83]86 Mefenamic acid (Hmef), a nonsteroidal anti-inflammatory drug, is used as an effective analgesic and antipyretic. Several research groups have reported metal complexes with mefenamic acid as ligands and have evaluated their biological activities.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the necessary parameters to be considered in cytotoxicity studies is the selectivity of the test agents between cancer and healthy cells [32][33][34]. In this context, as seen in Table 1, the [Ag(nif)(3-pic)] complex displayed much higher selectivity on cancer cells when compared to normal cells, and the highest selectivity was determined against HT-29 cells with an SI value of 4.67, followed by MDA-MB-453 (SI: 3.82) and A-549 (SI: 2.74) cells, respectively.…”
Section: Cytotoxicitymentioning
confidence: 99%